Studi Pengembangan Perbankan Syariah di Indonesia: Mengapa Masyarakat Tidak Memilih Bank Syariah? - Rahayu Saraswati; MB Hendrianto (Universitas Islam Indonesia, 2012)
Indonesia has been developing Islamic Banking since 1992. As the biggest muslim population in the world, it is expected that Islamic bank will have a significant role in the whole national banking system. A number of regulations have been issued by government and Bank Indonesia to accelerate the growth of Islamic Banking. Two most influential Islamic organizations –Majelis Ulama Indonesia and Muhammadiyah- have also issued fatwa on the haramness of interest and interest based banking. The fact shows, however, that the growth of Islamic Banking is not as fast as expected. Although having above national growth rate, Islamic banking is still minority to the whole national banking system. For instance, in 2010 the asset proportion of Islamic banking is still less than 3 percent of national banking asset. The aim of this paper is to identify the problems and challenges of the growth of Islamic banking in Indonesia. More specific, a survey has been conducted to identify factors influencing society not to choose Islamic banking products. The result shows that most of society are conventionally rational. Religious aspects have nothing to do with choice decision. They did not choose Islamic banking products because of economic factors such as quality of services, pricing, banking technology, and office location. This findings conclude that exploitation of religious aspect to develop Islamic Banking is less relevantKeywords: Islamic banking, rational, economic factor, religious aspects